Pediatric traumatic brain injury : new frontiers in clinical and translational research - Anderson, Vicki Ed; Yeates, Keith Owen Ed (Cambridge medicine, 2010)
"This book, New Frontiers in Pediatric Traumatic Brain Injury, aims to evaluate what we have learned about TBI in childhood to date and, perhaps more importantly to articulate the challenges we face and how we should go forward in the future"--Provided by publisher.